Changes in taste perception and eating behavior after bariatric surgery‐induced weight loss in women. (6th December 2013) - Pepino, Marta Yanina; Bradley, David; Eagon, J. Christopher; Sullivan, Shelby; Abumrad, Nada A.; Klein, Samuel
<x xml:space="preserve">Abstract</x> Objective Roux‐en‐Y gastric bypass (RYGB) surgery causes greater weight loss than laparoscopic adjustable gastric banding (LAGB). We tested the hypothesis that RYGB has weight loss‐independent effects on taste perception, which influence eating behavior and contribute to the greater weight loss. Methods Subjects were studied before and after ∼20% weight loss induced by RYGB (n = 17) or LAGB (n = 10). The following have been evaluated: taste sensitivity for sweet, salty and savory stimuli, sucrose and monosodium glutamate (MSG) preferences, sweetness palatability, eating behavior, and expression of taste‐related genes in biopsies of fungiform papillae. Results Weight loss induced by both procedures caused the same decrease in: preferred sucrose concentration (−12 ± 10%), perceived sweetness of sucrose (−7 ± 5%), cravings for sweets and fast‐foods (−22 ± 5%), influence of emotions (−27 ± 5%), and external food cues (−30 ± 4%) on eating behavior, and expression of α‐gustducin in fungiform papillae (all P values <0.05). RYGB, but not LAGB, shifted sweetness palatability from pleasant to unpleasant when repetitively tasting sucrose (P = 0.05). Neither procedure affected taste detection thresholds nor MSG preferences. Conclusions LAGB and RYGB cause similar alterations in eating behaviors, when weight loss is matched. These changes in eating behavior were not associated with changes in taste sensitivity, suggesting other, as yet unknown, mechanisms are involved.